Preclinical Studies Comparing Efficacy and Toxicity of DNA Repair Inhibitors, Olaparib, and AsiDNA, in the Treatment of Carboplatin-Resistant Tumors - Herath, Nirmitha I.; Berthault, Nathalie; Thierry, Sylvain; Jdey, Wael; Lienafa, Marie-Christine; Bono, Françoise; Noguiez-Hellin, Patricia; Sun, Jian-Sheng; Dutreix, Marie (Frontiers in Oncology, 2019)
Purpose: Carboplatin is used to treat many cancers, but occurrence of drug resistance and its high toxicity remain a clinical hurdle limiting its efficacy. We compared the efficacy and toxicity of DNA repair inhibitors olaparib or AsiDNA administered alone or in combination with carboplatin. Olaparib acts by inhibiting PARP-dependent repair pathways whereas AsiDNA inhibits double-strand break repair by preventing recruitment of enzymes involved in homologous recombination and non-homologous end joining. Experimental Design: Mice with MDA-MB-231 tumors were treated with carboplatin or/and olaparib or AsiDNA for three treatment cycles. Survival and tumor growth were monitored. Toxicities of treatments were assayed in C57BL/6 immunocompetent mice. Circulating blood hematocrits, bone marrow cells, and organs were analyzed 10 and 21 days after end of treatment using flow cytometry and microscopy analysis. Resistance occurrence was monitored after cycles of treatments with combination of AsiDNA and carboplatin in independent BC227 cell cultures. Results: Olaparib or AsiDNA monotherapies decreased tumor growth and increased mean survival of grafted animals. The combination with carboplatin further increased survival. Carboplatin toxicity resulted in a decrease of most blood cells, platelets, thymus, and spleen lymphocytes. Olaparib or AsiDNA monotherapies had no toxicity, and their combination with carboplatin did not increase toxicity in the bone marrow or thrombocytopenia. All animals receiving carboplatin combined with olaparib developed high liver toxicity with acute hepatitis at 21 days. In vitro, carboplatin resistance occurs after three cycles of treatment in all six tested cultures, whereas only one became resistant (1/5) after five cycles when carboplatin was associated to low doses of AsiDNA. All selected carboplatin-resistant clones retain sensitivity to AsiDNA. Conclusion: DNA repair inhibitor treatments are efficient in the platinum resistant model, MDA-MB-231. The combination with carboplatin improves survival. The association of carboplatin with olaparib is associated with high liver toxicity, which is not observed with AsiDNA. AsiDNA could delay resistance to carboplatin without increasing its toxicity.